(untitled) (Eurasian Journal of Research, Development and Innovation, 2023)
According to the analysis carried out within the framework of modern sociohumanitarian knowledge in this article, it is this that is the main component that has an important influence on the formation of family entrepreneurship, and within the framework of general philosophical and socio-philosophical knowledge, sociologists, psychologists, economists, cultural scientists, by identifying the specific features of business ethics or family entrepreneurship and its inclusion in the range of problems studied by political scientists